Knowledge of Slope Concept in Mathematics Textbooks in Undergraduate Education - Tuluk, Güler (Sciedu Press, 2020)
This questions the prevailing approach in the presentation of the concept of slope in teaching undergraduate in Turkey. For this purpose, five mathematics textbooks, were analyzed for problems related to slope, and similarities and differences were revealed. First, the subjects related to the slope in the textbooks were categorized and examined within the context in which they were handled. Therefore, this study is a qualitative study that adopts the interpretive paradigm. These categories are discussed in the form of connectivity, exploration, and purpose using the study for the context (Rezat, 2006). Stump (1999; 2001b) and Moore-Russo et al. (2011) studies were used for cognitive development. These are determined as geometric ratio, behavioral indicator, property determiner, algebraic ratio, parametric coefficient, functional property, linear constant, real life, physical property and trigonometry. Representations of the process skills were chosen as algebraic expressions, tables, and graphics. The concept is discussed in the form of calculus. In the use of technology (Akkoyunlu, 2002; Schware & Jaramillo, 1998), BCS, Scientific and Graphing Calculators, Internet are arranged. Definition, justification, and explanation for performance are arranged. When textbooks are compared, Turkey's textbooks contains more algebraic expressions, the use of the grounds and explanations and real-life connection, contains applications that use more formulas, the description is to use less highlighted is technology, other math they do not explicitly state their links with the subject areas. In general, it was seen that translated textbooks were mostly related to real life, equipped with explanations and justifications requiring cognitive competencies, and proceeded harmoniously between the subject area's main ideas and related ideas. These books use multi-step solved problems. Turkish textbooks need to be reviewed in terms of their functional areas in terms of context, cognitive need, representations, technology, and performance.
Keywords: 4. Education